Effect of Consumers' Attitude on Buying Organic Products in Iran. Issue 3 (2nd April 2016) - Rahnama, Hassan
ABSTRACT: In this study, the effect of consumers' attitude toward buying organic products in local markets is investigated. The purpose of this study is to help contribute to the economic development of rural areas in Iran, specially the north. Ten demographic factors, including better taste, price, availability of supply markets, high quality, good health, proper behavior of sellers, adaptation to environment, advertising effect, and keeping up with the Joneses, were considered as effective attitudinal factors in buying of products. Data were collected through questionnaires, based on a sample of 405 specimens during 5 months. Dumb variables regression was used to test the hypotheses. Results showed that except for two factors (gender and residence), other factors have a significantly positive effect on purchasing. Consumers' satisfaction of price and ease of access to markets were interesting points of research; also proving the effect of keeping up with the Joneses on consumer purchasing is the most important finding of the research, studied for the first time on organic products.